GEOGRAPHICAL NAMES THAT PROVIDE INFORMATION ABOUT THE RELIEF AND ITS CHANGES (Scientific journal of the Fergana State University, 2024)
In this article, among the geographical names in the territory of our country, the oronims representing the relief form of the place, which have changed relatively little, are studied. Geographical terms meaning relief in toponyms of our country were also studied, their weight was determined and analyzed based on statistical data.